2011
DOI: 10.1038/eye.2011.212
|View full text |Cite
|
Sign up to set email alerts
|

Ocular injuries from improvised explosive devices

Abstract: Purpose To document the characteristics, treatments, and anatomical and functional outcomes of patients with ocular trauma from improvised explosive devices (IEDs). Methods Retrospective review of ocular injuries caused by IEDs, admitted to our tertiary referral centre. Results In total, sixty-one eyes of the 39 patients with an average age of 24 years (range, 20-42 years) were included in the study. In total, 49 (80%) eyes of the patients had open-globe and 12 (20%) had closed-globe injury.In eyes with open-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 23 publications
2
19
0
1
Order By: Relevance
“…The mean age of the casualties in this report (24.5 years) is similar to other reports of ocular trauma,4 19–22 and all of the casualties are men because female soldiers are exempted from military operations in the Turkish army.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The mean age of the casualties in this report (24.5 years) is similar to other reports of ocular trauma,4 19–22 and all of the casualties are men because female soldiers are exempted from military operations in the Turkish army.…”
Section: Discussionsupporting
confidence: 88%
“…This report confirms the severe visual loss observed following military ammunition explosions; a VA of NLP was found in 21.7% of the injured eyes compared with 37.3% in a mine-clearing operation19 and 36% in IED blasts4—the NLP VA in mine blasts in this report was 4/30 (13.3%). We believe that the higher frequency of NLP VA in mine-clearing operations is likely related to the closer proximity to the exploded mines, whereas the mine blasts detailed in our report generally occurred during deployments and had a greater stand-off distance from the mine blast accounting for the lower incidence of ocular injury.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Erdurman et al13 reported that 28% of patients with ocular injuries resulting from improvised explosive devices required DES as a primary surgical intervention. Several investigators2,13 have reported eye trauma as one of the most common indication for DES in the urban milieu. The main goal of a destructive procedure is the prevention of sympathetic ophthalmia which, from a pathophysiological perspective, is believed to be an immunologic response to the exposure of previously sequestered intraocular tissue 14.…”
Section: Discussionmentioning
confidence: 99%
“…IOFBs have been reported in 26%–76% of open globe injuries in combat eye trauma 4 7 8. Thach et al 1 evaluated IOFB injuries in military personnel and reported that the most common types of IOFB were metal (68%), glass (14%), stone/cement (14%), bone (5%) and cilia (3%); the origin of the bone fragments was unreported in this article.…”
Section: Discussionmentioning
confidence: 72%